GROWTH OF Schizolobium amazonicum (Huber ex Ducke) SEEDLINGS INOCULATED WITH ARBUSCULAR MYCORRHIZAL FUNGI - de Andrade, Alyce Vanessa Nunes; Santana, Jhonata Santos; da Silva, Jeferson Pereira; Rodrigues da Silva, Thayllon Ferro; Lima, Yasmim Maria Wolfart; da Silva, Wilson Araújo (Floresta, 2019)
Arbuscular mycorrhizal fungi (AMF) occur in large numbers of plant species, especially in tree plants, and are present in almost all tropical soils. Their inoculation enables faster seedling growth and a higher survival rate in the nursery, thereby anticipating the transplant to the field. Despite these advantages, there is little information available on the efficiency obtained from the combination of different mycorrhizal species. In view of this, this work had the objective to evaluate the development of Paricá (Schizolobium amazonicum) seedlings from the association with different combinations of AMF species: Rhizoglomus clarus, Claroideoglomus etunicatum and Gigaspora margarita, isolated and combined under greenhouse conditions. The design was completely randomized, with seven treatments and fifteen replications, totaling one hundred and five experimental units. Three evaluations were carried out during the experiment at 30, 60, 90 days after sowing. The evaluated variables were plant height (H), stem diameter (SD), number of leaves (NL), fresh shoot weight (FSW), dry shoot weight (DSW) fresh root weight (FRW), dry root weight (DRW), height/diameter ratio (H/D) and Dickson Quality Index (DQI). It was found that there was a significant response of the treatments studied at a 5% probability level for most of the evaluated parameters. The results obtained in the present work allowed to conclude that the use of a mixed inoculation of Rhizoglomus clarus + Gigaspora margarita promoted better development and growth in Paricá plants under greenhouse conditions.